Capsaicin 8% Patch Treatment in Non-Freezing Cold Injury: Evidence for Pain Relief and Nerve Regeneration - Anand, Praveen; Privitera, Rosario; Donatien, Philippe; Misra, V. Peter; Woods, David R. (Frontiers in Neurology, 2021)
Introduction: Neuropathic pain associated with Non-freezing Cold Injury (NFCI) is a major burden to military service personnel. A key feature of NFCI is reduction of the intra-epidermal nerve fibre density in skin biopsies, in keeping with painful neuropathy. Current oral treatments are generally ineffective and have undesirable side effects. Capsaicin 8% patch (Qutenza) has been shown to be well-tolerated and effective for reducing neuropathic pain, for up to 3 months after a single 30-minute application. Methods: In this single-centre open label study, 16 military participants with NFCI (mean duration 49 months) received 30-minute Capsaicin 8% patch treatment to the feet and distal calf. Pain symptoms were assessed using a pain diary (with the 11-point Numerical Pain Rating Scale, NPRS) and questionnaires, the investigations included skin biopsies, performed before and three months after treatment. Results: Participants showed significant decrease in spontaneous pain (mean NPRS: -1.1, 95% CI: 0.37 to 1.90; p=0.006), and cold-evoked pain (-1.2, 95% CI 0.40 to 2.04; p=0.006). The time-course of pain relief over 3 months was similar to other painful neuropathies. Patient Global Impression of Change showed improvement (p=0.0001). Skin punch biopsies performed 3 months after the patch application showed significant increase of nerve fibres with structural marker PGP9.5 (intra-epidermal nerve fibres [IENFs], p<0.0001; sub-epidermal nerve fibres [SENFs]; p=<0.0001), and of regenerating nerve fibres with their selective marker GAP43 (p=0.0001). The increase of IENFs correlated with reduction of spontaneous (p=0.027) and cold-evoked pain (p=0.019). Conclusions: Capsaicin 8% patch provides an exciting new prospect for treatment of NFCI, with regeneration and restoration of nerve fibres, for the first time, in addition to pain relief.